Inteligencia emocional y agresividad en estudiantes de educación primaria Institución Educativa Inicial Primaria Antonio Raimondi, distrito de Punchana 2022 - Canelo Apagueño, Almendra Antonia (2024)
The study presents as general objective; determine the relationship between emotional intelligence and aggressiveness in primary level students, Antonio Raimondi Primary Initial educational institution of the Punchana 2023 district, the methodology used was descriptive and field and as a cross-sectional correlational design, a sample of 183 students was considered. At the primary level, the survey was used as a technique and as instruments, for the emotional intelligence variable a Likert-type Scale and for Aggression the Aggression Scale of Martínez, et al. As a result, we have a Pearson correlation coefficient rxy= 0.644, indicating that there is a high, direct and positive relationship between both variables, concluding, emotional intelligence and aggressiveness are significantly related.